Prevalence of undernutrition and associated risk factors among under five children in rural Haldwani - Preeti,; Awasthi, Sadhana; Gupta, Rupali; Kanubhai, Thakkar Hemaben (Asian Journal of Medical Sciences, 2023)
Background: The foundation of any nation is children. Malnutrition in children is global issue that may have both short- and long-term irreversible negative health consequences and thus associated with morbidity and mortality. Aims and Objectives: The study aims to determine the prevalence and associated risk factors of under-nutrition among under-five children in rural area of Haldwani. Materials and Methods: A community-based cross-sectional study conducted on Four hundred children residing in the rural field practice area of the Department of Community Medicine, Government Medical College, Haldwani. Results: The prevalence of underweight, stunting, and wasting was 7.75%, 9.25%, and 4%, respectively among under five children. The risk factors found significantly associated with undernutrition and sociodemographic profile were family size, parent’s education, mother’s occupation, and the socioeconomic class. The maternal factors found significantly associated with undernutrition were intake of iron folic acid tablets during antenatal care and postnatal care period, duration of pregnancy, site of delivery. Prelacteal, colostrum given, exclusive breastfeeding, and age of introducing complementary feeding and occurrence of recurrent diarrhea, recurrent acute respiratory infection, and worm infestation were child characteristics and medical illness found significantly associated with undernutrition. Conclusion: In this study, 17.5% of children were found undernourished. Factors determining undernourishment were parents literacy, social class, type and size of family, iron folic acid taken during pregnancy, feeding practices, immunization status, history of recurrent diarrhea, and other infections in the past 1 year.